ANALISIS PENGARUH KUALITAS PELAYANAN MODUL PENERIMAAN NEGARA GENERASI KEDUA (MPN G2) TERHADAP KEPUASAN WAJIB PAJAK DENGAN MENGGUNAKAN METODE CUSTOMER SATISFACTION INDEX (CSI) - Hannie, Hannie; Sulistiyowati, Nina (Jurnal Pilar Nusa Mandiri, 2018)
Modul penerimaan Negara Generasi Kedua (MPN G2) is a state revenue system that uses electronic deposits. Where currently Taxpayers can be easier, faster and more accurate in fulfilling tax obligations by utilizing electronic facilities provided by the online Directorate General of Taxes. To determine the level of satisfaction of taxpayers on MPN G2 attributes, a satisfaction measurement process is required by using the Customer Satisfaction Index (CSI) method. The CSI measurement results can be used as benchmark in order to improve the Modul Penerimaan Negara Generasi Kedua (MPN G2) system. The data used are primary data and secondary data. The sampling method is the Non Probability Sampling method, while the Non Probability sampling method used is Purpose Sampling. The CSI calculation results for MPN G2 servant quality attributes is 90.61 percent. It means that the total satisfaction level between 81% - 100%, means that the taxpayer is very satisfied with the performance of MPN G2 service quality attributes.